Impact of ICT on Unemployment: A Global Empirical Analysis - Andar Ristabet Hesda (Jurnal Ketenagakerjaan, 2023)
This study explores the relationship between ICT development and the unemployment rate in a cross-country setup. The relationship between the development of ICTs and human labour has always been debated among researchers. The debate revolves around whether ICT substitutes or complements human labour. This relationship still has not ended at a meeting point. This study utilizes the ICT index from International Telecommunication Unit to capture broader coverage of ICT development in the country. This index arguably improves the accuracy and comparability of variable measurement. Furthermore, this research conducts a heterogeneity analysis of ICT's impact by considering the unemployed education level and the country's development stage. The empirical method employs in panel data setup, namely Fixed Effect Model. The data consist of 57 countries in the period 2015-2017. Interestingly, this study finds that ICT development corresponds to a decrease in total unemployment by 1%, with the largest effect on unemployed with medium education. By heterogeneity analysis, this beneficial effect is only applied in developed countries. The study results indicate that the developing country should be more cautious and adaptive in mitigating the rapid ICT waves.